Emergency Radiology c - Zagoria, Ronald J.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer.)
To advance and improve the radiologic aspects of emergency care To establish Emergency Radiology as an area of special interest in the field of diagnostic imaging To improve methods of education in Emergency Radiology To provide, through formal meetings, a mechanism for presentation of scientific papers on various aspects of Emergency Radiology and continuing education To promote research in Emergency Radiology by clinical and basic science investigators, including residents and other trainees To act as the resource body on Emergency Radiology for those interested in emergency patient care Members of the American Society of Emergency Radiology (ASER) receive the Emergency Radiology journal as a benefit of membership!
Keywords: Emergency medicine; Radiology; Imaging / Radiology; Emergency Medicine